Revolusi Pembelajaran Agama Islam Di Era Industri 4.0 : Peran Kecerdasan Buatan Dalam Menghadirkan Inovasi Pendidikan - Achmad Robith Khusni; Prof. Dr. H. Mundir, M.Pd; Prof. Dr. H. Mashudi; Dr. H. Moh. Sahlan, M.Ag (SIRAJUDDIN : Jurnal Penelitian dan Kajian Pendidikan Islam, 2024)
Abstract Artificial intelligence (AI) has brought a significant revolution in Islamic education. This is an interesting topic that deserves attention. Although AI presents great opportunities, the impact on the world of Islamic education must be carefully considered from the perspectives of its role, ethics, and application in the field of Islamic knowledge. The aim of this research is to detail the revolution, role, and innovations of artificial intelligence in the realm of Islamic education. The method used is a qualitative approach focusing on literature studies. The literature search is based on data sources such as Google Scholar and other relevant databases. The results of this study indicate that artificial intelligence can bring about a rapid revolutionary impact on Islamic education, including the use of chatbots for religious counseling, content recommendation systems for learning, and plagiarism detection in assignments related to Islamic material. The role of artificial intelligence in education is to create an adaptive learning experience that can be tailored to the difficulty level and teaching methods according to each student's abilities. Overall, artificial intelligence (AI) has tremendous potential to enhance productivity, efficiency, and the quality of learning across various fields, including education. By leveraging AI, we can create an innovative, adaptive, and effective learning environment that supports student development in this modern technological era.